2019
DOI: 10.1021/acsami.9b05197
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Enhanced Selective Adsorption of Gold Ions on Tannin-Coated Porous Polymer Microspheres

Abstract: Metal recovery from electronic waste and industrial wastewater has attracted increasing attention to recycle precious metals and inhibit the emission of hazardous heavy metals. However, the selective recovery of precious metals with a large quantity is still very challenging because wastewater contains a variety of different cations while precious metal ions are relatively scarce. Here, we introduce a simple method to selectively increase the adsorption of gold ions using tannin-coated porous polymer microsphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 69 publications
0
33
0
Order By: Relevance
“…This result demonstrates that the hydroxyl groups in TA are efficient at attracting and adsorbing the gold ions, as demonstrated in our previous work. 24,27 On the other hand, the k 2 values, which indicate the amount of adsorbent required to adsorb 1 mol of metal ions/min, decreased by a factor of 7.0 for TA−TiO 2 (1-sun) (0.08 g mmol −1 min −1 ) in comparison with TA−TiO 2 (dark) (0.56 g mmol −1 min −1 ). This result suggests that light leads to improved adsorption rates of gold ions, probably by reducing the gold ions, which is discussed in the following section.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result demonstrates that the hydroxyl groups in TA are efficient at attracting and adsorbing the gold ions, as demonstrated in our previous work. 24,27 On the other hand, the k 2 values, which indicate the amount of adsorbent required to adsorb 1 mol of metal ions/min, decreased by a factor of 7.0 for TA−TiO 2 (1-sun) (0.08 g mmol −1 min −1 ) in comparison with TA−TiO 2 (dark) (0.56 g mmol −1 min −1 ). This result suggests that light leads to improved adsorption rates of gold ions, probably by reducing the gold ions, which is discussed in the following section.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…25,26 Our recent work demonstrated that the photochemical activation of TA-coated polymer microspheres can facilitate the adsorption of metal ions. 27 However, the photochemical activity of TA was measured on an inert polymer substrate. This single-component photochemical reaction has limitations, such as undesirable backward reactions and reduction of light absorption by redox mediators.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[6] Because of its biocompatibility,o xidation resistance,a ntibacterial and anti-inflammation properties,a nd strong affinity with biomacromolecules such as DNA, collagen, gelatin and thrombin, TA has been employed to prepare numerous biomaterials. [7] Thehigh affinity between TA and biomacromolecules is attributed to multiple hydrogen bonds formed between the phenolic hydroxyl-rich moieties and target objects. [8] Additionally,w ith five galloyl groups and five catechol groups on each molecule,T Ac an coordinate with different kinds of metal ions to form metal-organic coordination polymers (MOCs).…”
Section: Introductionmentioning
confidence: 99%
“…However, it requires specialized equipment and generates hydrogen as a byproduct at the cathode surface under dilute conditions. Furthermore, electronic waste generally contains dilute noble metal ions together with metal ion contaminants [ 5 ]. New noble metal recovery processes should meet the following challenging criteria: (i) high metal element selectivity, (ii) one-pot operation, (iii) easy separation and (iv) a monophasic reaction in (homogenous) aqueous solution under dilute conditions (i.e., a sustainable chemical process).…”
Section: Introductionmentioning
confidence: 99%